2011
DOI: 10.1179/oeh.2011.17.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Non-fatal Occupational Injuries among Non-governmental Employees in Malaysia

Abstract: We analyzed data on non-fatal occupational injuries reported to Malaysia's social security organization from 2002 to 2006. There was a decrease in both the absolute number and the incidence rates of these injuries over time. About 40% of cases occurred in the manufacturing sector followed by the service (17%) and trading (17%) sectors. The agriculture sector reported the highest incidence rate (24.1/1,000), followed by the manufacturing sector subcategories of wood-product manufacturing (22.1/1,000) and non-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
1
15
1
Order By: Relevance
“…This finding is in agreement with the literature, which indicates risk two to three times greater for males 11,27,28,31 , although it has been demonstrated that women handling tools and animals are 49% more at risk in Colorado 32 . Diverse studies have found higher risk among individuals aged over 50 years 6,7,11,31,33 . This fact was not found in tobacco farming and perhaps this was influenced by the division of labour according to age, whereby more arduous and risky jobs are delegated to the younger.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is in agreement with the literature, which indicates risk two to three times greater for males 11,27,28,31 , although it has been demonstrated that women handling tools and animals are 49% more at risk in Colorado 32 . Diverse studies have found higher risk among individuals aged over 50 years 6,7,11,31,33 . This fact was not found in tobacco farming and perhaps this was influenced by the division of labour according to age, whereby more arduous and risky jobs are delegated to the younger.…”
Section: Discussionsupporting
confidence: 93%
“…In industrialized countries or farming involving greater mechanization, the main causes of accidents are falls, tractors, machinery and other equipment 11,12,21,41 . In this study there was a higher proportion of superficial injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total fatal and non-fatal accidents for Singapore were adjusted using the ratio of (100%/95.22% = 1.05). The fatal occupational injuries data of Malaysia were obtained from Abas et al [35], whereas non-fatal occupational injuries were obtained from Abas et al [36]. It is showed that around 75.49% of all fatal and non-fatal accidents in Malaysia are covered in these previous studies.…”
Section: Data Sources and Data Processingmentioning
confidence: 99%
“…of work-related injuries(Abas et al, 2011) About 9% of injuries were recurrent during the 10-year surveillance period.However, the percentage of recurrence of injuries decreased from 23 (9.6%) during the appraisal phase to 14 (8.2%) during the intervention phase, which was not significant. Based upon the 10-year surveillance study with its appraisal and intervention phases we can recommend that: -Workers must be educated about the potential hazards in working with machines.…”
mentioning
confidence: 99%